Role of socio-economic research in developing, delivering and scaling new crop varieties: the case of staple crop biofortification - Birol, Ekin; Bouis, Howarth E. (Frontiers in Plant Science, 2023)
The CGIAR biofortification program, HarvestPlus, aims to improve the quality of diets through breeding and scaling up of nutrient-dense varieties of staple food crops. Biofortification focuses on the primary role of agriculture to supply minerals and vitamins at affordable prices for national health. HarvestPlus has both research and development (R&D) and implementation arms. This paper explains the role of socio-economic research in each phase of the program from discovery to development, initial delivery, and going to scale, and how information generated through socio-economic studies has been instrumental to the success of the program. Ex ante and ex post benefit-cost analysis facilitated fundraising for initial biofortification research and scaling in each subsequent phase, as well as encouraged other public, private, and CSO/NGO stakeholders to take on and mainstream biofortification in their crop R&D, policies, and programs. Socio-economics research helped guide crop development by identifying priority crop-micronutrient-geography combinations for maximum impact. Health impacts of biofortification could be projected both by using empirical results obtained through randomized controlled trials conducted by nutritionists, and through famer-adoption models estimating impact at scale. Farmer and consumer surveys and monitoring systems provided the underlying information for estimating farmer adoption models and helped understand input/output markets, farmer and consumer preferences, and additional opportunities and challenges –all of which informed crop development and delivery activities, while building the knowledge base for scaling up biofortification.